Single – Photon Interference with Thermally Excited Three – Level Cascade Atoms - Al- Hilfy, A. (University of Thi-Qar Journal of Science, 2019)
A theoretical model is presented for a single – photon interference experiment in a beam - splitter using the second photon in a cascade transition of a three – level atomic system. A clear anticorrelation effect is found in the coincidences of photons on the two sides of the beam splitter that can only be explained by quantum theory of light . A qualitative comparison is made with an earlier single – photon interference experiment available in literature.